(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the risk level of falls among older inpatients using the Morse Fall Scale. Subjects and Methods: A cross-sectional descriptive study was conducted on 200 older adults (aged 60 and above) receiving inpatient treatment at the Department of Internal Medicine A – Geriatrics, Nghe An General Friendship Hospital in 2024. Results: The study recorded that 53.5% of participants were at high risk of falling, while 41.5% were at low risk. The most common chronic conditions included hypertension (65%), post-stroke sequelae (28%), and diabetes mellitus (19.5%). At Morse score ≥45, 53.5% of patients had a high risk of falling and 41.5% of patients had a low risk of falling. Conclusion: The fall risk among hospitalized older adults was relatively high, indicating the need for individualized care and management plans based on fall risk levels to improve treatment outcomes and prevent adverse events in this vulnerable population.